Randomized trial of weight loss in primary breast cancer: Impact on body composition, circulating biomarkers and tumor characteristics. Issue 10 (5th September 2019) - Demark‐Wahnefried, Wendy; Rogers, Laura Q.; Gibson, Justin T.; Harada, Shuko; Frugé, Andrew D.; Oster, Robert A.; Grizzle, William E.; Norian, Lyse A.; Yang, Eddy S.; Della Manna, Deborah; Jones, Lee W.; Azrad, Maria; et al.
Abstract : Obesity adversely impacts overall and cancer‐specific survival among breast cancer patients. Preclinical studies demonstrate negative energy balance inhibits cancer progression; however, feasibility and effects in patients are unknown. A two‐arm, single‐blinded, randomized controlled weight‐loss trial was undertaken presurgery among 32 overweight/obese, Stage 0–II breast cancer patients. The attention control arm (AC) received basic nutritional counseling and upper‐body progressive resistance training whereas the weight loss intervention (WLI) arm received identical guidance, plus counseling on caloric restriction and aerobic exercise to promote 0.68–0.92 kg/week weight loss. Anthropometrics, body composition, blood and survey data were collected at baseline and presurgery ∼30 days later. Tumor markers (e.g., Ki67) and gene expression were assessed on biopsy and surgical specimens; sera were analyzed for cytokines, growth and metabolic factors. Significant WLI vs . AC differences were seen in baseline‐to‐follow‐up changes in weight (−3.62 vs . −0.52 kg), %body fat (−1.3 vs . 0%), moderate‐to‐vigorous physical activity (+224 vs . +115 min/week), caloric density (−0.3 vs . 0 kcal/g), serum leptin (−12.3 vs . −4.0 ng/dl) and upregulation of tumor PI3Kinase signaling and cell cycle‐apoptosis related genes (CC‐ARG; all p ‐values <0.05). Cytolytic CD56 dim NK cell expression was positively associated with weight loss; CC‐ARG increased with physical activity. Increased tumor (nuclear) TNFα and IL‐1β, CX3CL1 and CXCL1 gene expression was observed in the WLI. Tumor Ki67 did not differ between arms. Feasibility benchmarks included 80% accrual, 100% retention, no adverse effects and excellent adherence. Short‐term weight loss interventions are feasible; however, mixed effects on tumor biology suggest unclear benefit to presurgical caloric restriction, but possible benefits of physical activity. Abstract : What's new? Obesity adversely impacts survival among breast cancer patients. Preclinical studies demonstrate negative energy balance inhibits cancer progression; however, effects in patients are unknown. This is the first randomized controlled trial to assess the impact of a pre‐surgical weight loss intervention among early‐stage breast cancer patients. Results show the effects of acute negative energy balance on tumor biology, circulating biomarkers, and quality‐of‐life. Short‐term weight loss interventions are feasible; however, mixed effects on tumor biology suggest unclear benefit to pre‐surgical caloric restriction. Such interventions may be better timed after surgical resection, though cell cycle‐apoptosis and DNA damage‐repair scores support increasing physical activity.